Prediction of Suitable Habitat Locations for Sea Turtle Nesting Using Maximum Entropy Along the Coast of Kretek Subdistrict, Bantul Regency - Lestari, Rini Fathoni; Kamal, Muhammad; Wicaksono, Pramaditya (Jurnal Indonesia Sosial Sains, 2025)
Development along the southern coast of the Special Region of Yogyakarta, particularly in tourism zones, increasingly threatens sea turtle conservation and reduces the availability of suitable nesting sites. This study aims to model the suitability of sea turtle nesting habitats, analyze environmental variables influencing nesting preferences, and evaluate prediction results along the Kretek District coastline using Species Distribution Modeling (SDM) with the MaxEnt algorithm. Eleven environmental variables—such as slope, distance to vegetation, dunes, built-up areas, fallow land, agricultural land, roads, rivers, fishponds, and proximity to the sea—were derived from remote sensing data. The model produced an elongated suitability pattern along stretches of sand and fallow land, indicating that Depok, Pelangi, Cemara Sewu, Barchan, and Parangkusumo Beaches are generally suitable for nesting, while Parangtritis Beach is unsuitable due to intense human activity. The model achieved very high accuracy (AUC 0.981), with distance from sand being the most influential variable (66.5% contribution; 63.6% permutation importance). Evaluation results showed that increased human disturbance correlates with fewer nesting sites; Depok and Parangtritis Beaches had the lowest presence, while Pelangi Beach recorded the highest nesting activity with 43 locations.